The effect of special exercises accompanying massage on the transitional speed and breathing frequency of young soccer players (Journal of the College of Basic Education, 2023)
Summary of the research:The research aims to know the effectiveness of the effect of using a special exercise accompanying the method of recovery (massage) on the physical and physiological variable (transitional speed and breathing frequency) for youth football players under the age of (17-18) years. The researcher used the experimental approach for one group using pre and post measurement. For this group due to its suitability in achieving the goals and hypotheses of the research, as the experimental approach is considered one of the best scientific research methods for solving problems. The basic research in order to find out the extent of its suitability for the research sample and the selection of 5 young players for the control group, and one of the most important conclusions is that the use of exercises that accompany the means of recovery works to increase the recovery of the players in proportion to the training curriculum followed to reach higher efficiency in performance and raise the physical and physiological aspect of the young players in a positive way The study recommended the need to use a special exercise added to the hospital method after training, because it has a positive effect on the speed of recovery of the players.Keywords: exercises, massage, soccer, recovery, transitional speed